Scenario forecasting for students’ professional future - V. S. Tretyakova (Образование и наука)
Introduction. In a situation of instability and uncertainty around the world, ambiguity of information about the expectation of future events, it is very important to equip a young person with the skills of seeing his/her future, qualitatively new characteristics, demanded competencies that meet the needs of society and today’s students as the future employees. The solution of the tasks facing vocational education is seen in a new architecture of education, the main tool of which is construction of clear trajectory of learning and development. Such a trajectory is implemented in professional future scenarios, which represent forecasting student’s activity unfolding in time and space. Professional future forecasting scenarios are designed to regulate the choice of strategies and tactics of behaviour in accordance with personal meanings and goals that determine the direction of the student’s activities, taking into account factors affecting their alignment. Forecasting the professional future, which determines the socio-professional success of participants of educational and professional activity, is an actual scientific and practical task facing education today.                Aim. The present research aimed to develop scenarios for the professional future as a fundamental basis for students to build their personal trajectory of professional development both in the process of studying in an educational organisation and at the workplace.                Methodology and research methods. The leading idea of the research is the concept of forecasting the professional future, which is based on the correlation of knowledge and ideas about future professional activity with the reflection of one’s own professionally significant qualities, attitudes and value orientations. The basic idea of the current study is the concept of personalised education, it provides vectors for the development of the student activity and his/her transition from the current state to the desired by designing the logic of advancement along its own trajectory of professional development.                As a leading approach to forecasting the professional future, the author applied the cognitive approach as a process in a person’s mind about future professional activity, which is inextricably linked with cognitive categories: interests, attitudes, knowledge, beliefs, and value orientations of a person. Self-awareness of the future is based on the correlation of knowledge about a person’s future professional activity with the reflection of one’s personal meanings, significant qualities, attitudes and value orientations, which are the essence of a person’s cognitive activity.                Scenario planning was employed as the main research method. The scenario as a method and as an effective tool for planning a personal trajectory of professional development fixes a standard set of knowledge about the object, determines the direction and time perspective of life plans, and thereby ensures predictability and meaningfulness of actions in preparation for an uncertain future. When developing a structure of a typical forecasting scenario for the professional future of a student, the methods of design, modelling, forecasting, generalisation and classification were applied.                Results. The author has developed the structure of a typical forecasting scenario for the professional future of a student. It is established that this structure consists of four content blocks: 1) the desired image of the professional future of the student; 2) analysis of the student potential in accordance with the desired image; 3) the process of transition of the person from the current state to the desired (implementation of the trajectory of development, control); 4) evaluation of results (analysis of achievements, causes and consequences of changes; correction of the vector of development). Each block is represented by scenario structures and the results that need to be obtained in the process of its implementation.                Scientific novelty of the conducted research lies in development and arrangement of personal professional programmes of the student, taking into account such parameters that reflect the connection of mental representations about the future with the form available for direct observation.                Practical significance. The proposed structure of the forecasting scenario for the professional future is intended for students, who have a meaningful approach to their future and want to purposefully move towards achieving it. The obtained results will contribute to the personalisation of training through building by students their own development scenario, self-realisation, which will increase educational and professional success. The study sets specific tasks for educational organisations, and employers, who are really interested in the professional training of successful specialists and are focused on long-term cooperation.